2021
DOI: 10.3389/fendo.2021.671225
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Time of Ovarian Reserve Recovery After Laparoscopic Unilateral Ovarian Non-Endometriotic Cystectomy

Abstract: BackgroundLaparoscopic ovarian cystectomy is established as the standard surgical approach for the treatment of benign ovarian cysts. However, previous studies have shown that potential fertility can be directly impaired by laparoscopic ovarian cystectomy, diminished ovarian reserve (DOR), and even premature ovarian failure. Therefore, fertility-preserving interventions are required for benign gynecologic diseases. However, there are still little data on the time period required for recovery of ovarian reserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…It could mean that in reproductive age this female's window of opportunity to conceive may be shorter compared to females of the same age who have not undergone ovarian cystectomy. This result coincide with the findings of Li et al 10 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It could mean that in reproductive age this female's window of opportunity to conceive may be shorter compared to females of the same age who have not undergone ovarian cystectomy. This result coincide with the findings of Li et al 10 …”
Section: Discussionsupporting
confidence: 94%
“…7,9 Previous publications have shown a reduction in the ovarian reserve after a surgical intervention on the ovaries. [10][11][12][13][14][15] Ovarian reserve (OR) refers to the reproductive potential and reflects the number of follicles left in the ovary. 11 Cycle-day-independent anti-Mullerian hormone (AMH), follicle-stimulating hormone (FSH), and antral follicle counts (AFC) are used to determine the OR.…”
mentioning
confidence: 99%
“…Also the endometrioma itself may cause damage to the surrounding ovarian tissue, with decreasing serum AMH level 22 . Reduced ovarian reserve postoperatively is reported to recover at approximately 3–6 months 23 , 24 . Recovery of ovarian reserve could be attributed to the reperfusion of ovarian tissue, activation and rearrangement of ovarian follicles 2 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Hoang Tong et al found that unilateral ovarian cystectomy with a 43.4–48% decrease in serum AMH from 1 to 6 months after surgery was the same as the cystectomy results performed in the early follicular phase in this study [ 34 ]. Zhou Liu et al estimated the distance to restore ovarian reserve after laparoscopic unilateral ovarian cystectomy to be six months [ 35 ]. Urman et al found a significant decrease in AMH concentration and antral follicle count (AFC) one month after surgery, a reduction that persisted six months postoperatively [ 36 ].…”
Section: Discussionmentioning
confidence: 99%